United Kingdom : 2004 Article IV Consultation-Staff Report; Staff Statement; Public Information Notice on the Executive Board Discussion; and Statement by the Executive Director for the United Kingdom. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This 2004 Article IV Consultation highlights that United Kingdom's real GDP growth is estimated at about 3 percent in 2004 and is expected to stay stable at about 2 1\2 percent in 2005-06, in line with potential growth. Domestic demand remains the key driver of growth, underpinned by continued strong earnings growth and robust corporate profitability. Inflation expectations remain well anchored. Rising import prices are expected to push inflation toward the 2 percent target over the coming 2-3 years.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet